ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TERNAK SAPI PERAH KELOMPOK TANI TERNAK REJEKI LUMINTU DI KELURAHAN SUMURREJO KECAMATAN GUNUNGPATI SEMARANG - Ervina, Dita; Setiadi, Agus; Ekowati, Titik (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The study aimed to analyze the income of dairy cattle farm and analyze the factors that influence the income of dairy cattle farm in KTT Rejeki Lumintu in Sumurrejo Village, Gunungpati District, Semarang City. This study was conducted on November-Desember 2018 in Sumurrejo Village, Gunungpati District, Semarang City, which was selected purposively. The method used in this study was census method with 31 respondents. The data were analyzed by  using multiple linear regression and one sample t-test. The result of this study showed that the net income and famer’s income was higher than the Semarang City Minim was Waged (UMK) in 2018. Based on the results of multiple linear regression analysis obtained multiple equations Y = 15.858 + 7.913 X 1 – 8.085 X 2 + 6.875 X 3 – 2.385 X 4 + 0.527 X 5 with the value of determination coefficent (R 2 ) was 0.863. The result of F test simultaneously the independent variables which include the amount of lactation cattle corrected by the amount of dairy products, the price of cattle, labor wages, the price of milk, and the price of additional feed were very significant on the dependent variable of net income. T-test of the partial the amount of lactation cattle corrected by the amount of dairy products, the price of cattle, labor wages, and the price of additional feed were very significant on the net income, meanwhile the price of milk partially did not significantly affect to the net income. Keyword: breeder, dairy cattle, incom